2003
DOI: 10.1016/s0047-6374(03)00019-8
|View full text |Cite
|
Sign up to set email alerts
|

Age related changes in population of peripheral T cells: towards a model of immunosenescence

Abstract: In this paper, we presented the results of analysis of experimental evidence for the decline of the human immune system functioning with age using mathematical model of immunosenescence. The most prominent changes in this system are related to the decline in the T-cellular immunity. These include the decline in the nai;ve T cells generation rate, shrinkage of the volume of the peripheral lymphoid tissue, decline of absolute and relative concentrations of nai;ve T cells in the blood, shortening of the average t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…Aging process is also associated with minor or major changes in immune response profiles and co-expression and co-existence of mismatched or misdirected inflammatory mediators (e.g., TNF-, IL-6, IFN-,, IFNs, PGE2, etc) features that are characteristics of immunoscenescence involved in a wide range of chronic diseases (Davalos et al 2010, Ginaldi et al, 2005, Chung et al, 2008, Khatami 2008, 2011a, Nagai et al, 2010, Ren et al, 2009, Romanyukha and Yashin 2003, Sansoni et al, 2008, Sedivy et al, 2008, Serbina et al, 2008, Siffrin et al, 2007, Zhang 2010 (Figures 3 and 4). Briefly, low grade (unresolved or subclinical) inflammation and longevity are known as comorbidity and co-mortality risk factors in the genesis and progression of nearly all chronic illnesses.…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aging process is also associated with minor or major changes in immune response profiles and co-expression and co-existence of mismatched or misdirected inflammatory mediators (e.g., TNF-, IL-6, IFN-,, IFNs, PGE2, etc) features that are characteristics of immunoscenescence involved in a wide range of chronic diseases (Davalos et al 2010, Ginaldi et al, 2005, Chung et al, 2008, Khatami 2008, 2011a, Nagai et al, 2010, Ren et al, 2009, Romanyukha and Yashin 2003, Sansoni et al, 2008, Sedivy et al, 2008, Serbina et al, 2008, Siffrin et al, 2007, Zhang 2010 (Figures 3 and 4). Briefly, low grade (unresolved or subclinical) inflammation and longevity are known as comorbidity and co-mortality risk factors in the genesis and progression of nearly all chronic illnesses.…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
“…However, longevity and the rate of functional capacities of organ systems and susceptibility to chronic diseases vary in individuals, due to a combination of genetics, immunological or biological factors and the frequency of exposure to diverse environmental hazards. In an attempt to find a common forum on enormous amount of fragmentary information on the biology of chronic diseases that are linked to inflammation, highlights of major molecular theories of aging are outlined in the following (reviewed in Khatami 2009 (Deng et al, 2008, Ginaldi et al, 2005, Goronzy and Wevand 2005, Khatami 2009a, Nagai et al, 2010, Siffrin et al, 2007, Vasto et al, 2008, Zhang 2010 (Campisi 2011, Chidgev et al, 2007, Chung et al, 2008, Davalos et al, 2010, Deng et al, 2008, Gounaris et al, 2006, Khatami 2008a, Klein et al, 2009, Montavani et al, 2004, O'Brien et al, 2008, Romanyukha and Yashin 2003 (Figures 3 and 4). c. Hormones, Metabolites and Lipids in Biology of Aging: Aging process is associated with altered functions of important hormones (e.g., estrogen, progesterone, insulin, glucagon, androgen, andosterone, testosterone, thyroxine, glucocorticoids, epinephrine, cortisol, mineralcorticoids, dehydroepiandosterone-DHEA, etc) and hormone-like growth factors (e. g., IGF-1, FGF, EGF, VEGF, etc).…”
Section: Inflammation and Age-associated Diseasesmentioning
confidence: 99%
“…Previous modeling studies in the area of immunological memory and aging have considered questions relating to the longevity of memory (26), the repertoire of immune cells (27)(28)(29), and immunosenescence more broadly (30)(31)(32). However, these studies did not consider the loss of the immune repertoire during aging.…”
mentioning
confidence: 99%
“…Based on study in animal and human, it is generally accepted that the volume of true thymic tissue attains maximum size at puberty, after that, it decreases gradually (Shanker, 2004). Therefore, with ageing, the thymic tissue weakens as a source of naïve T lymphocytes (Romanyukha and Yashin, 2003). The reduced T cell output, together with an increase in apoptosis of naïve T-cells limits the ability of aged individuals to respond to newly encountered antigens (Leposavic et al, 2006).…”
Section: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%
“…The reduced T cell output, together with an increase in apoptosis of naïve T-cells limits the ability of aged individuals to respond to newly encountered antigens (Leposavic et al, 2006). The markedly reduced size of the naïve T-cell subpopulation together with an increased number of memory cells in the periphery, is a clear-cut characteristic of ageing in the immune cells (Romanyukha and Yashin, 2003). However, recently, Mocchegiani et al (2006) reported that certain nutrition might effects thymic physiology.…”
Section: Peripheral Blood Mononuclear Cellsmentioning
confidence: 99%